Keberagaman Makna Pembaca: Analisis Resepsi Infografis Media Online Tirto.id - Vincentius Dimas Sanubari (School of Communication Science and Media Business, 2023)
The lack of reading interest in Indonesia has prompted the media to adopt more creative approaches in delivering news, including the use of infographics. Tirto.id is an online media outlet that utilizes infographics as a means of presenting news. This study specifically focuses on examining the reception of readers when consuming Tirto.id infographics. The research methodology employed is qualitative research using Stuart Hall’s reception analysis approach. Reception analysis enables a deeper understanding of the various meanings that readers derive when consuming media, as well as the factors influencing the divergent interpretations among readers. Data for the study was obtained through interviews with six readers or followers of Instagram Tirto.id and selected to represent diverse backgrounds in terms of occupation, gender, age, and geographic location. The findings of the study indicate that four informants found the presence of infographics beneficial in facilitating their understanding of the news content. However, two informants expressed the need for the inclusion of quantitative data in the infographics, rather than relying solely on lengthy narratives. Hence, it was suggested that a combination of visual and numerical information be utilized. Furthermore, the six informants displayed varied interpretations and responses to the infographics based on their social backgrounds. In the case of the Cerdas Belum Tentu Kritis infographic: one response was categorized as dominant-hegemonic, three as negotiated, and two as oppositional. In the case of the infographics chosen by the informants: three responses were classified as dominant-hegemonic, and three as oppositional. Keywords: infographics, Tirto.id, reception analysis, Stuart Hall, diversity of meanings